Programa educativo "Educación Sexual" en el mejoramiento de competencias profesionales de los estudiantes de segundo nivel de la carrera de educación secundaria con especialidad en lengua y literatura de la facultad de ciencias de la educación y humanidades de la Universidad Nacional de la Amazonía Peruana Iquitos 2021 - Vásquez Vásquez, Javier (2022)
In the present work, the effect of the educational program "Sexual Education" was measured in the improvement of professional competences of the students of the first level of the Secondary Education Career with a specialty in Language and Literature of the Faculty of Educational Sciences and Humanities - Universidad Nacional de la Amazonia Peruana, Iquitos 2021. The research work was a longitudinal study with a pre-experimental design of pre-test and post-test type of a single group, that is, without a control group. The sample consisted of 22 students. The Educational Program had 12 classes, with the corresponding factors (knowledge, skills and attitudes) that make up the professional skills and with the content to achieve the development of each one of them. The input and output tests were carried out anonymously using Google forms, which is a software part of Google Workspace. The information was processed with the statistical program IBM SPSS (Statistical Package for the Social Sciences) version 25. The Shapiro-Wilk normality test and Student's t-test were used. It is observed that there is a substantial improvement in the medium to high levels and that there is no low level in the level of professional skills in favor of the exit test. It is concluded that the application of the educational program "Sexual Education" significantly improves professional skills (p-value =0.000 < ? = 0.05).